Neural-differentiated mesenchymal stem cells incorporated into muscle stuffed vein scaffold forms a stable living nerve conduit - Hassan, Nur Hidayah; Sulong, Ahmad Fadzli; Ng, Min-Hwei; Htwe, Ohnmar; H. Idrus, Ruszymah B.; Roohi, Sharifah; Naicker, Amaramalar S.; Abdullah, Shalimar (Orthopaedic Research Society, 2012)
Autologous nerve grafts to bridge nerve gaps have donor site morbidity and possible neuroma formation resulting in development of various methods of bridging nerve gaps without using autologous nerve grafts. We have fabricated an acellular muscle stuffed vein seeded with differentiated mesenchymal stem cells (MSCs) as a substitute for nerve autografts. Human vein and muscle were both decellularized by liquid nitrogen immersion with subsequent hydrolysis in hydrochloric acid. Human MSCs were subjected to a series of treatments with a reducing agent, retinoic acid, and a combination of trophic factors. The differentiated MSCs were seeded on the surface of acellular muscle tissue and then stuffed into the vein. Our study showed that 35–75% of the cells expressed neural markers such as S100b, glial fibrillary acidic protein (GFAP), p75 NGF receptor, and Nestin after differentiation. Histological and ultra structural analyses of muscle stuffed veins showed attachment of cells onto the surface of the acellular muscle and penetration of the cells into the hydrolyzed fraction of muscle fibers. We implanted these muscle stuffed veins into athymic mice and at 8 weeks post-implantation, the acellular muscle tissue had fully degraded and replaced with new matrix produced by the seeded cells. The vein was still intact and no inflammatory reactions were observed proving the biocompatibility and biodegradability of the conduit. In conclusion, we have successfully formed a stable living nerve conduit which may serve as a substitute for autologous nerves